Design, preparation, and characterization of bovine papillomavirus chitosan-based nanoparticles as a prototype for a bovine papillomatosis vaccine - RAQUEL ANDRESSA BRITO; CARLA A. SILVA; ANDRE C. AMARAL (Anais da Academia Brasileira de Ciências)
Abstract The bovine papillomavirus (BPV) is known to cause lesions in the epithelial tissue of cattle, which causes bovine papillomatoses. This disease is characterized by wart lesions in different body parts, causing losses in the animal value. Despite the economic impact, there are no effective vaccines available at this moment. The present study aims to develop a nanoformulated autogenous vaccine using the inactivated virus present in warts to control the diseases associated with BPV. To this end, papillomavirus was collected from infected bovines on a farm in Goiás, Brazil. The warts containing the viruses were macerated to obtain the inactivated viruses to be formulated within chitosan nanoparticles. The chitosan nanoparticles containing the inactivated viruses presented 330.7 nm in size, a polydispersity index of 0.41, and a positive Zeta potential of 38.2 mV. The association efficiency was 58.3%. The nanoparticles containing the inactivated virus were stable for up to 30 days and presented no hemolysis toxicity. This could be an interesting approach to develop a vaccine to protect bovines from BPV infection.